2020
DOI: 10.1038/s41598-020-67298-7
|View full text |Cite
|
Sign up to set email alerts
|

An alternative interpretation of the slow KaiB-KaiC binding of the cyanobacterial clock proteins

Abstract: The biological clock of cyanobacteria is composed of three proteins, KaiA, KaiB, and KaiC. The KaiB-KaiC binding brings the slowness into the system, which is essential for the long period of the circadian rhythm. However, there is no consensus as to the origin of the slowness due to the pre-binding conformational transition of either KaiB or KaiC. In this study, we propose a simple KaiB-KaiC binding scheme in a hexameric form with an attractive interaction between adjacent bound KaiB monomers, which is indepe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…The comparison between the hexameric and monomeric models shows that the simultaneous promotion and acceleration of the complex formation arises from the cooperative binding of six KaiB to C1. Our previous study has shown that this cooperative binding originates from the attractive adjacent KaiB-KaiB interaction in the KaiB-KaiC complex [20]. In particular, this KaiB-KaiB interaction much more largely stabilizes the KaiB 6 KaiC 6 complex than the other smaller complexes KaiB n KaiC 6…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The comparison between the hexameric and monomeric models shows that the simultaneous promotion and acceleration of the complex formation arises from the cooperative binding of six KaiB to C1. Our previous study has shown that this cooperative binding originates from the attractive adjacent KaiB-KaiB interaction in the KaiB-KaiC complex [20]. In particular, this KaiB-KaiB interaction much more largely stabilizes the KaiB 6 KaiC 6 complex than the other smaller complexes KaiB n KaiC 6…”
Section: Discussionmentioning
confidence: 93%
“…Remarkably, in light of the kinetic theory [19], the result indicates that the pre-binding conformational transition of KaiC is the rate limiting process. Moreover, we have theoretically shown that the slow KaiB-KaiC binding of the former experiment can be explained by the attractive KaiB-KaiB interaction in the ring-shaped KaiB-KaiC complex [15], without assuming the slow conformational transition of KaiB [20]. Thus, it is now conceivable that the slowness of the binding arises from KaiC rather than KaiB.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Since only KaiB fs is active (Tseng et al, 2017), this phenotypic readout suggests that the low abundance of KaiB fs probably plays an important role in maintaining the cyanobacterial circadian clock. The mechanistic details of this role are still up for debate, however (Chang et al, 2015;Koda and Saito, 2020).…”
Section: Regulation Through Fold Switching Ii: Kaib In a Cyanobacterimentioning
confidence: 99%